2009
DOI: 10.1002/hep.23192
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of resistance to the protease inhibitor boceprevir in hepatitis C virus–infected patients†

Abstract: Boceprevir is a hepatitis C virus (HCV) nonstructural protein (NS) 3/4A protease inhibitor that is currently being evaluated in combination with peginterferon alfa-2b and ribavirin in phase 3 studies. The clinical resistance profile of boceprevir is not characterized in detail so far. The NS3 protease domain of viral RNA was cloned from HCV genotype 1-infected patients (n ‫؍‬ 22). A mean number of 47 clones were sequenced before, at the end, and after treatment with 400 mg boceprevir twice or three times daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
269
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 288 publications
(282 citation statements)
references
References 23 publications
9
269
2
2
Order By: Relevance
“…We read with interest the article by Susseret et al 1 They successfully showed the characterization of resistance to boceprevir in patients infected with hepatitis C virus (HCV) genotype 1. 1 In the near future, antiviral effects in HCV infection genotype 1 for the combination of boceprevir with various drugs (interferon, statins, and ribavirin) would be considered by replicon systems.…”
Section: An Indicator For Evaluating the Risk Of Cancerous Transformamentioning
confidence: 99%
See 2 more Smart Citations
“…We read with interest the article by Susseret et al 1 They successfully showed the characterization of resistance to boceprevir in patients infected with hepatitis C virus (HCV) genotype 1. 1 In the near future, antiviral effects in HCV infection genotype 1 for the combination of boceprevir with various drugs (interferon, statins, and ribavirin) would be considered by replicon systems.…”
Section: An Indicator For Evaluating the Risk Of Cancerous Transformamentioning
confidence: 99%
“…1 In the near future, antiviral effects in HCV infection genotype 1 for the combination of boceprevir with various drugs (interferon, statins, and ribavirin) would be considered by replicon systems.…”
Section: An Indicator For Evaluating the Risk Of Cancerous Transformamentioning
confidence: 99%
See 1 more Smart Citation
“…13,15,16 In addition to these positions, the use of boceprevir has been associated with the emergence of resistance at positions 55 and 170. 14 Here we report the findings from a subanalysis of the Phase 3 telaprevir REALIZE trial, in which treatment outcomes and the emergence of viral variants were further characterized in patients with prior peginterferon/ribavirin treatment failure who did not achieve an SVR with subsequent telaprevir-based therapy. We explored whether the use of a peginterferon/ ribavirin lead-in, HCV genotype subtype, or prior peginterferon/ribavirin response category had an effect on treatment outcome or the emergence of variants.…”
mentioning
confidence: 99%
“…Therefore, during treatment with DAAs, such as telaprevir and boceprevir, there is the potential for selection of preexisting viral variants with decreased susceptibility to DAAs with a similar mechanism of action. [13][14][15] In HCV genotype 1-infected patients, the use of telaprevir was associated with the emergence of resistant variants at NS3 amino acid positions 36, 54, 155, and 156. 13,15,16 In addition to these positions, the use of boceprevir has been associated with the emergence of resistance at positions 55 and 170.…”
mentioning
confidence: 99%